How can I solve this?

#csc^2x tan^2x -1 = tan^2x#

#csc^2x tan^2x -1 = tan^2x#

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
Feb 17, 2018

we know that, #cscx=1/sinx# and that, #tanx = sinx/cosx#
Applying the same.

#csc^2x xx tan^2x−1=tan^2x #

#LHS=[1/cancel(sin^2x) xxcancel(sin^2x)/cos^2x]−1#

#=1/cos^2x−1#

#=sec^2x−1#

#=tan^2x#

Was this helpful? Let the contributor know!
1500
Trending questions
Impact of this question
41 views around the world
You can reuse this answer
Creative Commons License